Y⁴ + 12y² + 36
Now factorize the expression
y⁴ + 6y² + 6y² + 36
= y²(y² + 6) + 6(y² + 6)
= (y² + 6) (y² + 6)
<span>Now 6 is not the perfect square and according to rule, binomial can not be factored as the difference of two perfect squares.
</span>so multiply both.
(y² + 6)² is the answer.
Its 36 because 4×9=36 and 12×3 is 36. hope this helps.
Answer:
111 students because they like to drink good water
Step-by-step explanation:
BLAHHHHHHHHHHHHHHHHHHHHHHHHHHHHHHHHHHHHHHH
Slope = (y2-y1)/(x2-x1)
(3+1)/(2-0) = 4/2 = 2
The slope is 2